Determination of Radon Level in Drinking Water in Mehriz Villages and Evaluation the Annual Effective Absorbed Dose - Mohammad Malakootian; Hasan Salmani Marvast (Shahid Sadoughi University of Medical Sciences, 2015)
Introduction: Radon is one of the most radioactive elements that may be found in soil, air and water naturally. Presence of fault and also granitic rocks near the water sources can cause high radon levels in these water resources. Radon concentration of various drinking water sources And network In Mehriz Villages was measured from Anar- Mehriz fault and granite stone of Shirkooh area. Material and Methods: This was a cross sectional research that was conducted in fall of 2013 on the sources of drinking water and also drinking water network of Mehriz villages of Yazd province. After sampling and sending samples to the laboratory, radon concentration was measured by RAD7 device. According to the measured radon levels, the annual absorbed dose was also calculated. Results: Radon concentrations of samples ranged from 0.187 BqL-1 to 14.8 BqL-1.These results were related to samples No.12 and 9 and also to aqueducts of Tang-e-chenar and Malekabad village respectively. Based on the amount of radon in the sample, the lowest annual effective absorbed dose through drinking water or breathing(In an environment where water was used) was 0.0005msv/y and the maximum amount was 0.04msv/y. Conclusion: Apart from samples No.9 and 16 that were elated to the aqueduct of Malekabad village and a private well in Dare Miankoohvillagehaving48 persons as total population, Radon concentrations of other samples used by people of Mehriz villages as drinking water was low and less than permitted limit set by the Environmental Protection Agency of United States of America.